Media strategy and military operations in the 21st century mediatizing the Israel Defence Forces - Shavit, Michal (Contemporary security studies, 2017)
Following the end of the Cold War and European Union enlargement, in what sense does Eastern Europe continue to exist as a meaningful geo-political concept? In addressing this question, contributors to this volume-Alex Cistelecan, Robert Bideleux, Katalin Miklóssy and Dieter Segert-tease out the implications for an 'Area Studies' approach to the region.